COVID-19, Knowledge, Attitude and Practice among Students in a Tertiary Care Center, Nepal - Luitel, Abhinaya; Agrawal, Santosh Kumari; Regmee, Pragya; Devkota, Amrit (Journal of BP Koirala Institute of Health Sciences, 2022)
Background: Health care professionals are thought to be knowledgeable about contemporary happenings in health around the world. We aimed to assess knowledge, attitude, and practice (KAP) regarding coronavirus disease 2019 (COVID-19) and compare it among dental and medical students of a University hospital, B. P. Koirala Institute of Health Sciences (BPKIHS), Dharan, Nepal. Methods: A cross-sectional study was conducted among dental and medical students of BPKIHS. A google form was designed using standardized validated 25 item questionnaire pertaining to knowledge, attitude and practice regarding COVID-19. Following ethical approval, the questionnaire was sent through email to all dental and medical students, reminder mail was sent for three times and the response was collected. The data was analyzed for frequency and percentage. Chi-square was imputed for proportion differences between streams. Results: Out of all 602 students of BPKIHS, one did not give consent and only 240 (BDS 116; MBBS 124) (39.93%) agreed and responded. Overall, 72.1% of correct responses were obtained from all the students on knowledge regarding COVID-19. Moreover, the correct response for each question was similar between BDS and MBBS students, (p > 0.05). Most of the students (87.91%) reflected a positive attitude and 91.83% abided by safe practices during this pandemic. Conclusion: Although only 72.1% of the responses on knowledge related questions were correct, the majority showed positive attitude and practiced to minimize the spread of COVID-19 infection. Moreover, dental and medical students had a similar level of knowledge regarding COVID-19.